Application of an on-line sensor to map soil packing density for site specific cultivation - Shamal, S. A. M.; Alhwaimel, Saad A.; Mouazen, Abdul Mounem (Elsevier, 2016)
Tillage is the most energy consuming operation in the primary production in agriculture. The majority of farmers worldwide adopt homogeneous tillage operations to optimise crop establishment, reduce weeds and compaction, where soil disturbance took place across the entire field including areas where no soil preparation is needed. This practice consumes high energy and leads to decrease soil resistance to water and air erosion. This paper investigates the potential of a previously developed on-line soil bulk density (BD) sensor to map packing density for the delineation of management zones for site specific tillage. The on-line sensor consisting of a multi-sensor platform pulled by a tractor was used to measure soil BD in two experimental fields with potato in East Anglia, UK. It consisted of a load cell to measure subsoiler draught, a wheel gauge to measure depth and a visible and near infrared (vis-NIR) spectrophotometer for the measurement of moisture content (MC). Based on these three on-line measured parameters, BD was calculated using a previously developed model with a hybrid numerical and multivariate statistical analysis. The packing density (PD) was then calculated for all on-line measured points as a function of BD and clay content (CC). Maps of soil BD and PD were produced, and both fields were divided into management zones with different tillage recommendations. Results, in the studied fields, showed that the on-line BD sensor can map not only the spatial distribution in BD but enable estimation of PD too. Classifying the PD into three compaction classes revealed that only 4.8% of the field needs aggressive tillage (primary and secondary tillage) and about 34.8% of the field requires harrowing or surface loosening with a cultivator (reduced tillage), while the remaining area of the field do not need any sort of tillage. Virtual calculations of fuel consumption and CO2 emission in one field based on the three PD classes confirmed that site specific tillage would significantly reduce energy consumption and CO2 emission, as compared to reduced and conventional tillage practices. By this it can be concluded that the on-line multi sensor platform for the assessment of PD holds a great potential for mapping and managing soil compaction site specifically. A future study is needed to relate soil compaction to actual plant growth and yield, and evaluate cost of production and practical limitations of this approach.
Keywords: Packing density; Soil compaction; Site specific tillage